Perjalanan sukses PT. Kelola Mina Laut Unit Sampang: Strategi dan tantangan dalam pengelolaan sumber daya yang berkelanjutan - Aini, Qurrotul (Maliki Interdisciplinary Journal, 2024)
Kelola Mina Laut Sampang Unit has demonstrated a successful journey in managing marine resources with sustainability-focused strategies. This article reviews the strategies used by company to maintain a balance between marine resources exploitation and environmental preservation. These strategies include marine resource conservation, research and innovation, and partnerships with local communities. Despite achieving success, the company also faces challenges such as climate change, strict regulations and conflict management. However, with a strong commitment and holistic approach, PT Kelola Mina Laut Unit Sampang has become an inspiring example for other industries in their efforts towards sustainable marine resource management.